2013
DOI: 10.1155/2013/259458
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dissipation and the High‐Strain Rate Dynamic Response of Vertically Aligned Carbon Nanotube Ensembles Grown on Silicon Wafer Substrate

Abstract: The dynamic mechanical behavior and high-strain rate response characteristics of a functionally graded material (FGM) system consisting of vertically aligned carbon nanotube ensembles grown on silicon wafer substrate (VACNT-Si) are presented. Flexural rigidity (storage modulus) and loss factor (damping) were measured with a dynamic mechanical analyzer in an oscillatory three-point bending mode. It was found that the functionally graded VACNT-Si exhibited significantly higher damping without sacrificing flexura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…The individual CNT forests were fabricated using the wellestablished method of floating catalyst chemical vapor deposition (FC-CVD) [24][25][26][27][28] on silicon wafers [Wafer World, Inc., 100 mm diameter, Type P Boron doped (100) orientation, Palm Beach County, FL, USA] cut to a size of about 6 mm by 60 mm in a quartz reactor (2 in. diameter and 38 in.…”
Section: Experimental Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual CNT forests were fabricated using the wellestablished method of floating catalyst chemical vapor deposition (FC-CVD) [24][25][26][27][28] on silicon wafers [Wafer World, Inc., 100 mm diameter, Type P Boron doped (100) orientation, Palm Beach County, FL, USA] cut to a size of about 6 mm by 60 mm in a quartz reactor (2 in. diameter and 38 in.…”
Section: Experimental Methods and Proceduresmentioning
confidence: 99%
“…The CNT growth process was continued for 30 min. The process time of 30 min was selected based on previous CNT growth studies [26][27][28]. After the 30-min process time, the precursor solution and H 2 flow were turned off while the N 2 flow rate was set to 1000 mL/min to flush the residual chemical species from the reactor.…”
Section: Experimental Methods and Proceduresmentioning
confidence: 99%
“…In a following study where the silicon wafer covered with a CNT forest was tested, the mechanism for the enhanced damping was discussed. The primary energy dissipation is also believed to be a general result of the interfacial friction between individual CNTs, caused by their entanglements under cyclic deformation …”
Section: Vibration Damping In Carbon Nanotube Assembliesmentioning
confidence: 99%
“…Besides such effect of intertube friction, the CNT entanglement plays more important roles in determining the viscoelasticity. (Even in CNT forests, the effect of entanglement is still non‐negligible …”
Section: Vibration Damping In Carbon Nanotube Assembliesmentioning
confidence: 99%
“…It was observed that VACNT based sandwich composites showed higher flexural rigidity and damping compared to samples consisting of carbon fiber fabric stacks without VACNT. In previous research [8] conducted at the Blast and Impact Dynamics laboratory, University of Mississippi, the dynamic mechanical behavior and high strain-rate response of a FGM system consisting of VACNT grown on a silicon (Si) wafer substrate have been investigated. It was found that VACNT forests grown on Si wafer substrate exhibited significantly higher flexural stiffness, damping, and specific energy absorption.…”
Section: Introductionmentioning
confidence: 99%